Barbiturates and pyrazolopyridines for the treatment of postpartum depression—repurposing of two drug classes - Horwitz, Alexander B.; Rubin, Robert T. (Frontiers in Pharmacology, 2023)
Zulresso (brexanolone) is an aqueous formulation of the neurosteroid, allopregnanolone, and the only FDA-approved medication for the treatment of postpartum depression (PPD). While brexanolone is effective for the treatment of PPD, lengthy infusion time and high cost can be prohibitive. Failure of GABAA receptors to adapt to fluctuating neurosteroid levels is considered to predispose women to mood disorders in the postpartum period. Brexanolone is thought to act via stimulation of δ subunit-containing GABAA receptors, which are extrasynaptic and localized to particular brain regions. Neurosteroid stimulation of δ subunit-containing GABAA receptors leads to sustained inhibition (hyperpolarization) of GABAergic neurons, which makes δ subunit-containing GABAA receptors a potentially important pharmacologic target. Barbiturates and pyrazolopyridines are potent stimulators of δ subunit-containing GABAA receptors and therefore potentially cost-effective treatments for PPD. Barbiturates are often not prescribed, owing to risk of dependence and respiratory depression. The pyrazolopyridines were tested several decades ago for anxiety and depression but never developed commercially. Herein we use the FDA-approved dosing schedule of brexanolone and GABAA receptor binding data from various animal models to examine the safety, efficacy, and potential clinical utility of barbiturates and pyrazolopyridines for the treatment of PPD. We suggest consideration of repurposing barbiturates and pyrazolopyridines as safe and readily available treatment alternatives for PPD.